Rapid Flow Cytometry-Based Test for the Diagnosis of Lipopolysaccharide Responsive Beige-Like Anchor (LRBA) Deficiency - Gámez-Díaz, Laura; Sigmund, Elena C.; Reiser, Veronika; Vach, Werner; Jung, Sophie; Grimbacher, Bodo (Frontiers in Immunology, 2018)
The diagnosis of Lipopolysaccharide-Responsive Beige-like-Anchor-Protein (LRBA) deficiency currently relies on gene sequencing approaches that do not support a timely diagnosis. We developed a rapid, sensitive and functional test for implementation at clinical immunology laboratories. This test is based on the detection of LRBA protein by flow cytometry in peripheral blood cells after stimulation. LRBA protein was assessed in a prospective cohort of 54 healthy donors and 57 patients suspected of LRBA deficiency who were recruited in our diagnostic center. ROC (Receiver Operating Characteristics) analysis suggested an LRBA: MFI ratio cut-off point of 2.6 to identify LRBA-deficient patients by flow cytometry with 94% sensitivity and 80% specificity, and to discriminate them from patients with a similar clinical picture but other disease-causing mutations. This easy LRBA flow-cytometry-based assay allows a fast screening of patients with suspicion of LRBA deficiency reducing therefore the number of patients requiring LRBA sequencing and accelerating treatment decisions. Detection of biallelic mutations in LRBA is however required for a definitive diagnosis.